Pemberdayaan Penyandang Disabilitas dalam Mewujudkan Hak Pekerjaan yang Layak oleh UKM Tiara Handicraft Surabaya - Dewi Austine Britania; Agus Widiyarta (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This study describes the Empowerment of Persons with Disabilities in Realizing the Right to Decent Work by UKM Tiara Handicraft Surabaya. Persons with disabilities in society tend to experience discrimination and are seen as unable to work or hinder work in their daily lives, causing persons with disabilities to not get jobs. With the existence of small and medium enterprises that empower people with disabilities, namely UKM Tiara Handicraft Surabaya, they are able to prove the quality of their workforce can be taken into account in the world of work and increase community participation to be able to help improve their quality of life with voluntary assistance such as in the medical, educational, financial and other fields. etc. So this study aims to find out the process of empowering people with disabilities and the supporting factors and obstacles in realizing decent work rights by UKM Tiara Handicraft Surabaya. This study uses a Qualitative Research Method based on existing problems and is considered the most appropriate and appropriate to describe the problems that occur and uses several data collection techniques, namely Interview, Observation, Documentation, and Library Studies. The results of the study show that the empowerment of persons with disabilities in realizing the right to decent work by UKM Tiara Handicraft Surabaya has been carried out well although there are still several inhibiting factors.